Childhood vitiligo developing after COVID-19 infection - Gianmaria Viglizzo; Astrid Herzum; Lodovica Gariazzo; Camilla Olcese; Corrado Occella (PAGEPress Publications, 2023)
Coronavirus disease 2019 (COVID-19) and COVID-19 vaccinations have been linked to immune cutaneous manifestations, mostly presenting similar clinical pictures.1 Among immune skin reactions associated with COVID-19 vaccines, hypopigmentations and vitiligo have been extensively reported.2 Conversely, reports of vitiligo following COVID-19 itself are scarce up to date, completely lacking in children.3,4 Herein we present a case of childhood vitiligo developing shortly after COVID-19 infection.